The Interpretations of The Theotokias by The Patriarch John Ibn Qiddis - Youhanna Nessim Youssef (New Jersey Gorgias Press, 2020)
"The theotokias are prayers dedicated to the Virgin Mary, the Mother of God (Theotokos). In the early fourteenth century, the Patriarch of the Coptic Church, Ibn Qiddis, composed and paraphrased - in Coptic - the Theotokias. His work has only survived in a single manuscript. This book introduces the author, John Ibn Qiddis, his liturgical, pastoral, and literary activities, and the Coptic language of his time, followed by the texts and an English translation"--
Ibn Qiddīs active 14th century Theotokias
Keywords: Liturgy -; Coptic language -- Texts; Theology